2015
DOI: 10.2218/resmedica.v23i1.1216
|View full text |Cite
|
Sign up to set email alerts
|

Communication With Ventilated Patients In ICU: Perceptions On Existing Communication Methods And Needs

Abstract: Introduction: Recent research has highlighted the need to improve communication with mechanically ventilated patients. There are a number of studies currently evaluating the usefulness of augmentative and alternative communication methods (AACs), but a significant gap still exists in understanding patients' key needs during the ventilation period. Aims: 1) To determine the perceptions of patients and healthcare staff on the use of AACs. 2) To find out patients' key needs during ventilator treatment, within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Fourth, our findings show three different AAC approaches may be useful in the ICU: unaided AAC, aided low‐tech AAC, and aided high‐tech AAC. Studies that examined the communication methods used by mechanically ventilated patients reported that unaided approaches mostly encompassed the use of yes/no signals as the dominant strategy and aided AAC was rarely applied (Happ et al., 2011; Sii & Swann, 2015). Unaided AAC may be the dominant approach as mechanically ventilated patients experience a greater level of physical weakness and fatigue and fluctuate in the level of consciousness and/or cognition, thus unable to use advanced AAC (Holm & Dreyer, 2018b; Sii & Swann, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our findings show three different AAC approaches may be useful in the ICU: unaided AAC, aided low‐tech AAC, and aided high‐tech AAC. Studies that examined the communication methods used by mechanically ventilated patients reported that unaided approaches mostly encompassed the use of yes/no signals as the dominant strategy and aided AAC was rarely applied (Happ et al., 2011; Sii & Swann, 2015). Unaided AAC may be the dominant approach as mechanically ventilated patients experience a greater level of physical weakness and fatigue and fluctuate in the level of consciousness and/or cognition, thus unable to use advanced AAC (Holm & Dreyer, 2018b; Sii & Swann, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated the gap in the literature that exists regarding nurses' concerns when it comes to communicating with patients who have a diminished level of consciousness. These circumstances are incompatible with delivering high‐quality, secure, and patient‐centered care 6 . It is highly advised to maintain a positive attitude, be a good listener, and grasp patients' needs by using appropriate skills to improve communication 9,10 along with providing useful and ethical care 11 …”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest problems for patients with a decreased level of consciousness (DLOC) today is the breakdown in nurse‐patient communication. In ICUs, nurses have a special relationship with patients and play a crucial role in communicating with patients who are unable to speak 6 . According to Holm & Dreyer (2018), communicating with a patient who has a lower level of consciousness revolves around two emotions: frustration and open communication 7 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations